Formative assessment in the translation classroom: Closing a feedback loop - Sofiya Nikolaeva; Tetiana Korol (Institute of Advanced Engineering and Science, 2021)
Feedback as the key component of formative assessment was studied extensively in the context of the acquisition of the foreign language productive skills by different categories of learners. Similarly, this paper aimed at the investigation of the optimal design of the feedback loop in teaching translation to undergraduate students. A mixed-methods research involved 40 sophomores of Poltava University of Economics and Trade and was conducted during 2018–2019 academic year. It examined the efficacy of four feedback response types from both quantitative and qualitative perspectives. Sample Group 1 had to study the received teacher feedback arbitrarily and consider it, while working on their further translations. Sample Group 2 was required to prepare a written free-form self-reflection report on the teacher feedback. Sample Group 3 was supposed to resubmit their corrected translations to the teacher. Finally, Sample Group 4 had to accompany their self-reflection reports with the corrected translations. The obtained data showed statistically significant difference between the acquired levels of the translation skills by the students of the four sample groups. The highest results were achieved due to the combination of self-reflection reports and translation correction. The questionnaire on the students’ attitude to these practices proved the received statistical data.